Emerging materials in photonics applications - Sin Jin Tan; Sulaiman Wadi Harun; Yunzheng Wang; Zian Cheak Tiu (Materials Research Express)
The revolutionary discovery of graphene in 2004 paved the way for a range of innovative materials, unlocking new possibilities in photonics engineering. The extraordinary properties of these emerging materials include high optical responsivity, broad optical wavelength operation, fast recovery, and strong nonlinearity. These properties have significantly advanced the field of photonics engineering, such as optical light sources, photodetectors, optical modulators, optical sensors, and other photonics applications. This focus issue is dedicated to highlight the latest research on the applications of emerging materials in photonics, which have contributed to industrial growth in photonics engineering. The papers collected for this issue explore a broad array of applications, addressing critical areas such as (a) optical light source (b) optical light detector (c) optical modulation (d) optical sensing and material characterization, and (e) optical limiter.